The views of social workers and special guardians on planning contact for special guardianship children. Issue 4 (15th October 2019) - Thompson, Nicholas
Abstract : Purpose: Special guardianship order (SGO) assessments require social workers to make plans and recommendations for ongoing post-SGO contact between the child and the parents. However, there is very little policy to inform and guide practitioners on how these duties should be undertaken, and no studies that describe current practice. The purpose of this paper is to investigate how the recommending of contact in special guardianship cases is currently working, by holding focus groups with social workers and special guardians. This paper reports on the results of a study to examine what contact plans social workers are recommending, the thinking behind their decisions and the views of the special guardians who have to make those plans work. Design/methodology/approach: The research involved a mixed methods approach comprising of an online questionnaire, two focus groups for social workers and two focus groups for special guardians. This paper describes the second part of the study and reports on the qualitative results from the four focus groups. The methodology was based on a pragmatist theoretical position, and used an interpretivist approach and elements of the analytical procedure of grounded theory in order to generate inductive research. The focus group method was chosen as the best way to gather rich information on the opinions and ideas of practitioners who are recommending contact and the carers who are managing it. Findings: Participants provided a wide range of views on the issues, with practitioners describing the challenges of planning contact, and special guardians explaining the problems they faced with the parents. Involving special guardians in the study gave a chance to include the different perspectives of the people who have to make the contact recommendations work, and contrast their views on contact planning with those of the professionals. The study makes recommendations for practice, which recognise the difficulty of preparing an initial contact plan that will remain relevant for years ahead. Research limitations/implications: The number of focus groups the author held was limited by the author's own personal resources and the time the author had available, and one group only had three social workers on the day. The author's involvement affected the responses, and the author's questions dictated the issues that were commented on, but the answers were the opinions that the participants wanted to express. The nature of the approach means that no two sets of focus group results would ever be the same. And as the direction of the discussions was largely dictated by the participants, the coverage of all aspects of contact was probably inconsistent. Practical implications: This research sheds light on a crucial area of social work permanency planning, that has suffered from a lack of previous research, in order to better inform future practice. The paper reports on what contact plans social workers are recommending, the thinking behind their decisions and the views of the special guardians who have to make those plans work. It concludes with recommendations for improving future special guardianship policy and practice. Social implications: The research clearly raises a number of specific difficulties faced by special guardians and problems with current policy and practice. These include the special guardians' lack of understanding about contact, the difficulty for social workers of long-term planning, the challenge posed by uncooperative parents who behave badly, the view of carers for the need for a greater emphasis on the quality and reliability of contact, and the challenge to careful contact planning posed by the adversarial court process. Originality/value: Special guardianship has had a major impact on permanency planning since its introduction 12 years ago. However, apart from one DfE study in 2014, very little research has been produced to inform policy and practice. There have been no studies specifically on contact in special guardianship cases, despite contact being one of the two major factors in determining the success of SGO placements. This study has provided the first in-depth evaluation of social worker contact planning in special guardianship, and the first investigation of special guardians' views on contact.